Pendidikan Kesehatan Teknik Relaksasi Benson terhadap Penurunan Tingkat Kecemasan di Ruang Perawatan Bedah RSUD Raden Mattaher Jambi - Rahmadhani, Dwi Yunita; Yesni, Marnila; Al Fajri, Jufri (Jurnal Abdimas Kesehatan (JAK), 2024)
Surgery is a medical procedure that involves surgery on the body to improve a person's health function. The operation includes physiological preparation, namely general physical health status, nutritional status, fluid and electrolyte balance, cleanliness of the stomach and colon, shaving the surgical area, personal hygiene, emptying the bladder and preoperative exercises, apart from that, psychological preparation or mental preparation is also an important aspect. which is no less important in the process of preparing for surgery because the client's mentality is not ready or more can affect the client's physical condition. Efforts to overcome anxiety at the prevention and therapy stages require a holistic approach method, which includes physical (somatic), psychological or psychiatric, psychosocial and psycho-religious. These include increasing immunity to stress by improving nutrition, and psychopharmacological therapy that is often used is anti-anxiety drugs (anxiolytics). Benson relaxation is included in breathing relaxation (diaphragmatic breathing) which involves the client's belief factors, which can create an internal environment that can help clients achieve a higher state of health and well-being. Therefore, community service activities aim to improve the quality of public health and reduce anxiety levels by providing information to reduce the high level of anxiety of clients and families. This activity will be carried out in September 2022 – February 2023 in the Surgical Room at Raden Mattaher Hospital, Jambi. The targets of this activity are patients and families who are treated in the surgical room. Total participants 10 people. The output of this service activity is an improvement in the quality of public health so that people can live healthily and independently without feeling anxious and published in national journals.